2020
DOI: 10.1016/j.ejmp.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Simple low-cost approaches to semantic segmentation in radiation therapy planning for prostate cancer using deep learning with non-contrast planning CT images

Abstract: Deep learning has shown great efficacy for semantic segmentation. However, there are difficulties in the collection, labeling and management of medical imaging data, because of ethical complications and the limited number of imaging studies available at a single facility. This study aimed to find a simple and low-cost method to increase the accuracy of deep learning semantic segmentation for radiation therapy of prostate cancer. Methods: In total, 556 cases with non-contrast CT images for prostate cancer radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, the low soft tissue contrast and resolution in low-dose noncontrast-enhanced CT images of PET/CT provide a more difficult challenge in obtaining a clear automated volumetric segmentation of small organs. The performance of our aPROMISE algorithm in prostate segmentation in low-dose CT, without contrast, was similar to that of Nemoto T et al who also demonstrated a mean Dice score of 0.79 for prostate [22]. The Dice score of the bones and the visceral organ were observed to be 0.88 or above, indicating a much better performance of the algorithm in larger organs.…”
Section: Discussionsupporting
confidence: 83%
“…However, the low soft tissue contrast and resolution in low-dose noncontrast-enhanced CT images of PET/CT provide a more difficult challenge in obtaining a clear automated volumetric segmentation of small organs. The performance of our aPROMISE algorithm in prostate segmentation in low-dose CT, without contrast, was similar to that of Nemoto T et al who also demonstrated a mean Dice score of 0.79 for prostate [22]. The Dice score of the bones and the visceral organ were observed to be 0.88 or above, indicating a much better performance of the algorithm in larger organs.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies [ 112 , 114 , 122 , 123 ] have investigated the use of deep learning for the task of predicting dose distribution of the cancer treatment in the prostate gland. Kandalan et al [ 112 ] employed a 3D U-Net for dose prediction for volumetric-modulated arc therapy (VMAT) using PTV and OARs contours in prostate cancer.…”
Section: DL Methods By Anatomical Application Areasmentioning
confidence: 99%
“…Their model achieved a dice score of 0.88 and a precision of 76% on malignant and 75% on benign classes for the classification task using an Inception v3 architecture. The authors in [ 89 ] proposed a 2D U-Net model deploying CT images of 556 cases of prostate cancer. They achieved a dice score of 0.85, 0.94, and 0.85 for three organs, namely, prostate, bladder, and rectum, respectively.…”
Section: Current Applications Of Deep Learning In Cancer Diagnosis Prognosis and Predictionmentioning
confidence: 99%